In Algebra, you always need to separate the variable by itself. So, you need to always think of how you can do this. First always simplify both sides of the equation, if needed be. In case of Q1, it already is simplified. Therefore, you need to let the variable stand alone, by itself. Just the letter by itself.
a) MULTIPLY 5 to both sides of the equation. It is like a mirror. Whatever you do on one side, you have to do on the other side. That will leave you with
25=4-3y
b) ADD 3y to both sides of the equation. This will leave u with
3y+25=4
NOTE: This is what i call switching. You just switched -3y to the other side of the equation, and made it its oppposite sign, which is positive (+) 3y. Do not forget changing the sign or you'll get the wrong answer. Those are points on the exams.
c) SUBTRACT 25 to both sides of the equation. That will leave u with
3y=4-25 (which is equal -21), so the new equation is
3y= -21
d) DIVIDE 3 (coz you want you variable y to be alone by itself) to both sides of the equation. And that will leave you with
y= -7
Therefore, the answer is...well...just pick the that matches...
You can DOUBLE CHECK (and this is always a good idea to make sure you got the right answer). Just replace -7 with variable y, and you the equation should equal to 5 on both sides
5=5
2007-02-01 05:21:00
·
answer #1
·
answered by formula350 2
·
1⤊
0⤋
1. none of the answers; I think Knightofeth has the right idea
2. A. 7/17
1. 5 = 4-3y/5
Subtract 4 from each side, then multiply each side by 5 and divide by -3:
5 - 4 = 4 - 3y/5
1 = -3y/5
1 * 5 = -3y/5 * 5
5 = -3y
5 ÷ (-3) = (-3y) ÷ (-3)
-5/3 = y
and that is not a choice. In fact, I put each value into variations on the equation (5y=4-37/5, 5y=4y-37/5, 5=4-37/y, 5=4-3/y) and none of the answers checked out. So... I think the correction is wrong or the answers are.
2. 2x - 2 = 5(x-3)/11
Multiply both sides by 11 and then multiply out the 5*(x-3). Subtract the resulting 5x from each side and subtract the (-22) from each side. Finally, divide each side by 17.
2x - 2 = 5 * (x-3) ÷ 11
11 * (2x - 2) = {5 * (x-3) ÷ 11} * 11
22x - 22 = 5 * (x - 3)
22x - 22 = 5x - 15
22x - 22 -5x - (-22) = 5x - 15 - 5x - (-22)
17x = 7
17x ÷ 17 = 7 ÷ 17
x = 7/17
2007-02-01 04:57:41
·
answer #2
·
answered by roynburton 5
·
0⤊
0⤋
Question 1 doesn't make sense.
Question 2 :
2x -2 = 5(x-3)/11
22x - 22 = 5x - 15 --multiplying through by 11
17x = 7 --adding 22 to both sides
x = 7/17 --dividing through by 17.
i.e. A.
edit: first answer
with the equation you gave 5 = 4 - 3y/5 simplifies to y = -5/3, not an option so I think you meant
5 = (4-3y)/5
25 = 4 - 3y --multiply through by 5
21 = -3y --takeaway 4 from both sides
y = -7 -- simplify down
i.e. D.
2007-02-01 04:38:10
·
answer #3
·
answered by Kirstin 2
·
0⤊
0⤋
2. 2x-2 = 5(x-3) / 11
ans
11[2x-2] = 5(x-3)/11
22(x-1) =5(x-3)
22x – 22 = 5x – 15
22x -5x = 22- 15
17x = 7
x = 7/17
2007-02-01 04:41:55
·
answer #4
·
answered by Loki 2
·
0⤊
0⤋
number 1 is written wrong ... you need a variable
2. 2x-2 = 5(x-3) / 11
2x-2 = (5x-15) / 11
2x -2 = 5x/11 - 15/11
2x = 5x/11 - 15/11 +2
2x = 5x/11 - 4/11
2x - 5x/11 = -4/11
22x/11 - 5x/11 = -4/11
17x/11 = -4/11
cross multiply
187x = -44
x = -44/187
x = -4/17
none of the above
2007-02-01 04:36:47
·
answer #5
·
answered by Bill F 6
·
0⤊
2⤋
I can't understand what you are talking about.
2007-02-01 04:38:02
·
answer #6
·
answered by rwbblb46 4
·
0⤊
1⤋